Dynamics in amine-functionalized mesoporous hybrid materials probed through deuterium magic angle spinning NMR and molecular dynamic simulations - Veena, V. S.; Kavya, I; Lazar, A.; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Journal of Physical Chemistry C, 2020)
We present a deuterium magic angle spinning (MAS) NMR study on two widely used hybrid materials (3-glycidyloxy propyl)trimethoxysilane (3-GPTMS) and 3-(trimethoxysilyl)propyl methacrylate (3-MATMS) grafted on SBA-15. Methylene-deuterated diamine as a pendent group is anchored to GPTMS (O3Si-CH2-CH2-CH2-O-CH2-CH(OH)- CH2-NH-CD2-CD2-NH2) and MATMS (O3Si-CH2-CH2-CH2-O-C(N-CD2-CD2-NH2)-C(CH3)=-CH2) postgrafting. Proton and deuterium solid state NMR experiments under MAS were performed at two hydration levels and temperatures ranging from 253 to 315 K. Deuterium spectra were deconvoluted into three A Dr, components with different average quadrupolar parameters: a relatively rigid component arising from local or librational motion of C-H-2(2) corresponding to ``small angle'' jumps, an intermediate dynamic component, and a large amplitude dynamic component. Population ratios of rigid versus dynamic components show that diamine-MATMS is more rigid when compared with diamine-GPTMS at high hydration. The role of the length of the linkers, steric hindrance, grafting concentration, etc. in defining mobility is investigated. Finally, by correlating proton and deuterium MAS NMR spectral analysis, the role of a few water molecules in inducing dynamics of the linkers was investigated. Molecular dynamic (MD) simulations support the experimental analysis. MD simulations indicate different types of mobility arising from the same molecular binding configuration of diamine-MATMS. Dynamics induced by a few hydroxyls on the pore surface accessible to the linker, various molecular conformations, and stabilization of the linker through hydrogen bonding with the surface, derived from MD simulations, are discussed.